Knowledge and Attitudes of Patients and Their Relatives Toward Electroconvulsive Therapy in China. Issue 4 (29th May 2015) - Li, Yang; An, Feng‐Rong; Zhu, Hui; Chiu, Helen F. K.; Ungvari, Gabor S.; H. Ng, Chee; Lai, Kelly Y. C.; Xiang, Yu‐Tao
Abstract : Purpose: To examine the knowledge and attitudes of patients and their relatives as well as patients' subjective experience with electroconvulsive therapy (ECT) in China. Design and Methods: Up to 420 responders including patients receiving ECT ( n = 210) and their relatives ( n = 210) were assessed with self‐reported questionnaires. Findings: Patients and their relatives did not receive adequate information before ECT, particularly about the mode of its delivery, risks, and adverse effects. The most common adverse effect of ECT reported by patients was memory impairment. Both patients and their relatives had positive attitudes toward ECT and appeared satisfied with its therapeutic effects. Practice Implications: Mental health professionals need to address the inadequate information on ECT provided to patients and their relatives prior to the treatment.